“Everyone Can Master the Correct Use of Mathematical Methods”: The Relevance of L.D. Kudryavtsev’s Ideas for Modern Mathematics Education - A. L. Semenov; A. E. Abylkassymova (Высшее образование в России)
The article discusses the ideas, devoted to mathematics education, of Lev D. Kudryavtsev, corresponding member of the USSR Academy of Sciences, professor-mathematician. These ideas are based on more than half a century of practical experience of L. D. Kudryavtsev at the Moscow Institute of Physics and Technology – he presented his vision of the problems of educating students, the unity of mathematics, as well as methods of teaching it in the collection of articles. The thoughts and ideas of L. D. Kudryavtsev are still relevant today, in the age of digital transformation of the education system and of the entire life of society.